Evaluation of Health Related Quality of Life of Chronic Liver Disease Patients (Hbv & Hcv Related) (Journal of Chittagong Medical College Teachers' Association, 2019)
Background: One of the leading causes of death and disability worldwide is viral hepatitis and Hepatitis B (HBV) & Hepatitis C (HCV) constitute 90% of it. In chronic diseases it is more important to evaluate personal impact and disability caused by the disease. Objective: Purpose of this study was to assess the impact of HBV &/or HCV related Chronic Liver Disease (CLD) on health related quality of life of patients, providing insight on present condition of the patients. Materials and methods: This observational study was conducted from June to July, 2018 a private chamber of Chattogram, Bangladesh. Convenience sampling method was used to collect data from 112 HBV &/or HCV patients using EQ-5D-3L questionnaire. SPSS version 23 for windows was used for statistical analysis. Results: In our study, most of the patients could take proper care of themselves but almost one fourth complains some difficulty in walking (28.6%) and performing daily activities (25%). Whereas more than half of total participants had mild physical discomfort or pain (55.4%) and depressive or anxiety (51.8%) experiences in their life. We also found lower quality of life score (Mean 7.13, SD 1.531) in a scale of 5-15 with a comparatively higher well being score (Mean 72.23, SD 21.62) in scale of 0-100 among participants. It was also evident that vaccination status of the spouse were lower in patients with higher wellbeing perception. Conclusion: We tried to evaluate the HRQoL of HBV and HCV related CLD patients to mitigate the burden and provide equitable health care.JCMCTA 2019 ; 30 (1) : 31-35